Striving for musical excellence: a study on the development of music players' skills for church worship accompaniment through ensemble training - Putra Andino Nugrahhu; Ratih Sulistyowati; Ni Nyoman Astrini Utami; Jose Ernest (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
The connection between music and the church is integral, especially during worship, where hymns require musical accompaniment. The musical experience influences congregational engagement and emotions. Given the significance of musical accompaniment, diversity is essential. Coaching can enhance musicians' skills and contribute to varied worship experiences. This action research aims to guide music players at GKE Palangka I Palangka Raya to improve their music-playing skills, which are carried out in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of this study were ten teenage music players. Data were collected through observation, documentation, and skill tests. The data were analyzed by processing scores of assessment aspects, including the ability to imitate sounds, read notation, tempo suitability, intonation accuracy, and fingering techniques. The results increase musicians' skills in playing music through ensemble music, with an increase in the average score of each participant from pre-cycle 52 to the first cycle 62 by 19% and from the first cycle 62 to the second cycle 77 by 24%. This research contributes to the significance of musical diversity in worship, the impact of musical instruments on congregational engagement, and the potential benefits of coaching in enhancing musicians' skills for diverse music presentations, particularly within small musical ensembles. Additionally, this research highlights the significance of a theological-oriented approach to training in music ministry and practice and the potential for collaborative music training to improve musical proficiency in the context of worship.